2021
DOI: 10.1177/15579883211044306
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Pilot of a Technology-Based Intervention in the United States for Father’s Mental Health in the Perinatal Period

Abstract: Paternal mental health is increasingly recognized as an important public health issue, with about 10% of men experiencing depression perinatally. Paternal depression is associated with less responsive parenting, greater parenting stress, and suboptimal child development. In response to a lack of existing interventions that directly focus on fathers’ mental health in the United States, we developed and pilot tested the Fathers and Babies (FAB) intervention for use with partners of women enrolled in home visitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The adapted MBC was overall feasible and acceptable as an intervention to address mental health for mothers during the critical early childhood period in Kenya and Tanzania. Our work in adapting and modifying the MBC in Kenya and Tanzania is consistent with previous work that has systematically documented the cultural and contextual adaptations of the MBC with different populations (e.g., Central American immigrant mothers in the United States [20], Tribal American mothers [21], and fathers [12,22]). Collectively, this body of work has found that the process of adaptation is culturally humble, iterative, and has the potential for adoption from the communities impacted.…”
Section: Discussionsupporting
confidence: 84%
“…The adapted MBC was overall feasible and acceptable as an intervention to address mental health for mothers during the critical early childhood period in Kenya and Tanzania. Our work in adapting and modifying the MBC in Kenya and Tanzania is consistent with previous work that has systematically documented the cultural and contextual adaptations of the MBC with different populations (e.g., Central American immigrant mothers in the United States [20], Tribal American mothers [21], and fathers [12,22]). Collectively, this body of work has found that the process of adaptation is culturally humble, iterative, and has the potential for adoption from the communities impacted.…”
Section: Discussionsupporting
confidence: 84%
“…These findings provide many opportunities for intervention with depressed fathers. Given the success of home visiting programs for supporting mothers in the perinatal period, Hamil and colleagues [ 36 ] devised a Fathers and Babies (FAB) intervention to address their partners. The program is designed with the same cognitive behavioral therapy and attachment principles employed in the highly effective Mothers and Babies (MB) program for maternal postpartum depression prevention, as well as collected input from fathers, mothers, and home-visiting clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…It is also particularly important to note that improvements in childhood internalizing symptoms may lag behind parental improvements in depression; in one study the gap in time of improvements seen in children after remission of maternal depression was approximately six months [ 20 ]. Several innovative programs have been developed, such as the FAB [ 36 ] and Mom Power [ 44 , 45 ], that may model how to deliver parenting skills and parental therapeutic interventions for depression, however, further modalities for a variety of clinical settings and family structures should be explored and developed. Given the potentially lifelong impact of parental depression on offspring, it is imperative to continue to develop programs that decrease barriers to care, such as by providing targeted time-limited treatment and/or treatment in a digital format [ 17 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the expansion of the e–SBI-HV to address SU in partners and other family members is also a critical area of need. The engagement of fathers is a priority in HV research and practice [ 100 ] and enhancements to HV to address mental health in fathers have recently been developed [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…RenderX partners and other family members is also a critical area of need. The engagement of fathers is a priority in HV research and practice [100] and enhancements to HV to address mental health in fathers have recently been developed [101]. The next step in this research is to test the feasibility and preliminary efficacy of the e-SBI-HV.…”
Section: Xsl • Fomentioning
confidence: 99%